'A house for dead people': memory and spatial transformation in Red Location, South Africa. (19th May 2018) - Roux, Naomi
Abstract: One of several new South African post-apartheid memory projects, the Red Location Museum in New Brighton, Port Elizabeth opened in 2006, in a century-old informal settlement with strong histories of resistance. The museum was intended to acknowledge the area's contribution to the liberation struggle, and contribute to dismantling apartheid urban geographies by producing a tourist and cultural economy. However, the project was highly contested from its inception by residents who felt that the priority for the neighbourhood should be housing and service delivery. Major housing-related protests erupted on the museum's doorstep between 2003 and 2005, and in late 2013 the new cultural precinct was closed down indefinitely. This paper examines the politics and controversies surrounding the Red Location developments between 1997 and 2013, using this case study to consider the ways in which the protests around the museum are rooted in historical and political histories made visible through residents' radical claiming of ownership of the museum building. The Red Location example offers a useful consideration of the complexities of applying notions of 'participation' and 'community ownership' in practice in fraught situations where major change is needed, and makes a case for the thorough historicisation of contemporary conflicts over development and spatial change.